The Implementation Of Prosecution Termination Based On Restorative Justice In Traffic Accident Cases Resulting In Death Due To Negligence At The Asahan District Prosecutor's Office - Yosia Korintin Marpaung; Andry Syafrizal Tanjung; Syahranuddin (CERED Indonesia Institute, 2024)
Traffic accidents resulting in fatalities due to driver negligence are one of the crimes that often occur in Indonesia, including in Asahan Regency. In many cases, this incident was not done intentionally, but purely due to unplanned negligence (culpa).This type of research uses an empirical legal research method, this research combines a normative approach (statutory regulations and legal doctrine) and an empirical approach (observation of practices in the field), especially at the Asahan District Attorney's Office.Termination of prosecution based on restorative justice is regulated in the Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. This approach emphasizes the restoration of the original state and the restoration of relations between the perpetrator, victim, and community, rather than on retaliation through punishment. The application of termination of prosecution based on Restorative Justice to traffic accident cases due to negligence resulting in death at the Asahan District Attorney's Office in the application of restorative justice at the Asahan District Attorney's Office has been carried out in accordance with applicable regulations. In cases of traffic accidents due to negligence resulting in death, termination of prosecution can be carried out if the victim or his/her family has forgiven the perpetrator and a peaceful agreement is reached without any coercion or pressure and intimidation. The Public Prosecutor has an important role in facilitating this process and the Public Prosecutor as a facilitator ensures that formal and substantive requirements are met.